2021
DOI: 10.3390/ijms222011024
|View full text |Cite
|
Sign up to set email alerts
|

A Presurgical Study of Curcumin Combined with Anthocyanin Supplements in Patients with Colorectal Adenomatous Polyps

Abstract: Adenomatous polyps are precancerous lesions associated with a higher risk of colorectal cancer (CRC). Curcumin and anthocyanins have shown promising CRC-preventive activity in preclinical and epidemiological studies. The objective of this window-of-opportunity, proof-of principle trial was to evaluate the effect of curcumin combined with anthocyanin supplements on tissue biomarkers of colorectal adenomatous polyps. Eligible patients received either anthocyanin and curcumin supplementation or related matching p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…These derivatives have greatly expanded the clinical application prospects of CCM ( 31 ). Notably, regulation of the NF-κB pathway by CMM was confirmed in a clinical trial in which the combined use of anthocyanins and CCM significantly decreased the expression of NF-κB ( 32 ).…”
Section: Nuclear Factor Kappa B Signaling Pathwaymentioning
confidence: 92%
“…These derivatives have greatly expanded the clinical application prospects of CCM ( 31 ). Notably, regulation of the NF-κB pathway by CMM was confirmed in a clinical trial in which the combined use of anthocyanins and CCM significantly decreased the expression of NF-κB ( 32 ).…”
Section: Nuclear Factor Kappa B Signaling Pathwaymentioning
confidence: 92%
“…179,196,197 In another study, Meriva with anthocyanin has shown improvement in colorectal adenomatous polypos symptoms and it reduced NF-κB and Ki67 levels. 198 Further, another Meriva formulation called Algocur (each tablet contains 1g of Meriva) improved physical performance and reduced pain in men rugby players with osteo-muscular pain. 199 This formulation also showed to be safe and well-tolerated among these men.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with curcumin (3000 mg/day) for 12 months had no effect on polyp number and size in patients with familial adenomatous polyposis . Another study showed that presurgical curcumin (500 mg/day) with Mirtoselect (extract of Vaccinium myrtillus ) reduced NF-κB and Ki-67 expression in colorectal adenomatous polyposis ( n = 35) . A randomized, double-blind, and placebo-controlled clinical trial showed that administration of FLOVOMEGA (80 g/day) containing ascorbic acid, acetyl carnitine-l-HCl, baicalin, coenzyme Q10, phospholipidated curcumin, fructose, green tea catechins, and skullcap reduced serum CK levels and improved walking distance in 29 patients with Duchenne muscular dystrophy, Facioscapulohumeral dystrophy (FSHD), or Limb girdle muscular dystrophy (LGMD) …”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%